(untitled) (Research, Society and Development, 2020)
Forest cultivation of Eucaliptus spp. in Brazil it stands out due to its high adaptability, growth, and directed to the most diverse segments, making it the most cultivated species in the sector. With the advance of monoculture, the incidence of pests and diseases ends up being favored. S. cosmioides is one that causes great damage in several cultures, being mentioned about Eucalyptus seedlings, however, information about this culture is scarce, aiming to carry out this study. For that, leaves of clone I 144, the species Corymbia citriodora, Eucalyptus camaldulensise and artificial diet were used as a control, totaling 4 treatments and 5 repetitions with 10 caterpillars per repetition. The plants were conducted in pots in the greenhouse, aiming at exemption of chemical and phytosanitary products with good nutritional status from where the leaves were removed and supplied to the caterpillars. The consumption of E. camaldulensis was the one with the highest value, differing from the others, however it showed low weight of the caterpillars losing only to I 144, differing statistically from all. The treatment I144 provided the lowest values ​​of weight, size and duration of the larval phase, different from the other treatments, only the consumption was similar to that of C. citriodora, showing no statistical difference between them. Only the caterpillars fed with the diet and C. citriodora completed their cycle, passing to the pupa stage. C. citriodora may be the target of attack by S. cosmioides, the other eucalyptus tested in this study did not show potential for its development.